New Trade Strategy For the World Economy, Edited by Harry G. Johnson, George Allen and Unwin, London, 1969. (The Pakistan Development Review, 1973)
Harry G. Johnson edited the book under review when trade policy after the Kennedy Round was in a state of flux. In the United States there was a resurgence of protectionism. Britain suffered another EEC rebuff in the same period, with Western Europe remaining at Sixes and Sevens. The imbalance of European Currencies and the inadequacy of international reserves were a threat to international trade. Generalised Tariff Preferences for developing countries were agreed in principle, but agreement in practice was not in sight. President Kennedy's Grand Design needed a revision. A New Trade Strategy was required. The present collection of papers seems to have been designed to provide this new strategy. In broad terms, what is proposed is the establishment of a free trade regime in industrial products amongst a group of countries touching the Atlantic, together with some subsidiary proposals for action in related areas of trade policy. The nucleus of what would thus initially be a North Atlantic Free Trade Area (NAFTA) would be the United States, Canada and Britain and other members of the European Free Trade Associa¬tion (EFTA). But the plan would be an "open-ended" arrangement which other industrialised nations — Japan, Australia, New Zealand and the countries - of the European Economic Community—could also join, provided they were prepared to conform to the rules that this integration scheme would entail. The launching of a multilateral free trade association could be the means of continuing the momentum towards world trade liberalisation and of countering the inward-looking tendencies of the EEC.